'Why Do You Have to Look So Jewish All the Time?': Antisemitism and the Jewish Body in Howard Jacobson's Kalooki Nights. Issue 2 (1st September 2022) - Lander, Joshua
Abstract: This article parses the role of the body in Howard Jacobson's Kalooki Nights and the manner in which Jacobson satirically draws on antisemitic concepts of Jewish difference. The article explores the role of the body in Jacobson's magnum opus and how the author deconstructs the binaries that define and separate Jews and non-Jews. It offers new close readings of the novel that focus on the protagonist's failed marriages, and – following from David Brauner's recent monograph-length study – brings into focus new ways in which Jacobson's novel engages and departs from Philip Roth.